2013
DOI: 10.1002/ptr.4981
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study to Assess the Efficacy and Safety of a Citrus Polyphenolic Extract of Red Orange, Grapefruit, and Orange (Sinetrol‐XPur) on Weight Management and Metabolic Parameters in Healthy Overweight Individuals

Abstract: The present study investigated the efficacy and safety effects of Sinetrol-XPur (polyphenolic citrus dry extract) in weight management; metabolic parameters; and inflammatory, glycemic and oxidative status. In a 12-week, randomized, double-blind, placebo-controlled trial, Sinetrol-XPur was given to overweight subjects twice daily with meals in the tested group (N = 47) versus a placebo group (N = 48). Waist and hip circumference and abdominal fat were decreased in the Sinetrol-XPur group as compared with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 39 publications
2
50
1
4
Order By: Relevance
“…Studies have shown that polyphenols can exert part of their anti-inflammatory effects by decreasing the circulating levels of these proteins [59][60][61][62]. Interestingly, we recently reported that the offspring of dams treated with GSPE and fed a HFD during pregnancy and lactation showed attenuated plasma levels of MCP-1 in youth, demonstrating that procyanidins can program the offspring toward a better inflammatory profile [20].…”
Section: Discussionmentioning
confidence: 92%
“…Studies have shown that polyphenols can exert part of their anti-inflammatory effects by decreasing the circulating levels of these proteins [59][60][61][62]. Interestingly, we recently reported that the offspring of dams treated with GSPE and fed a HFD during pregnancy and lactation showed attenuated plasma levels of MCP-1 in youth, demonstrating that procyanidins can program the offspring toward a better inflammatory profile [20].…”
Section: Discussionmentioning
confidence: 92%
“…Evidence for the effects of polyphenols on obesity parameters in humans is inconsistent, possibly due to divergence among study designs, characteristics of the participants, and metabolic pathways. Although some intervention clinical trials with polyphenol-enriched food or polyphenol extracts do not show any effect on weight or waist circumference [10,11,12], other studies have reported that polyphenols reduce body weight and increase energy expenditure [13,14,15,16]. The oral bioavailability of polyphenols is particularly important because, after being modified and metabolized by enzymes, their concentration in tissues and biological fluids is quite low [9,12,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies show that polyphenols, such as from strawberries, 20 have an antioxidant function for cells. 40e42 CP could also have effect against oxidative stress 43 ; this suggests that the antioxidant property is one of the reasons for CP enhancing mitochondrial activity. Previous studies showed that fibroblasts would proliferate, migrating into the wound site in the short term.…”
Section: Discussionmentioning
confidence: 99%